1991
DOI: 10.1093/protein/4.6.669
|View full text |Cite
|
Sign up to set email alerts
|

Convex constraint analysis: a natural deconvolution of circular dichroism curves of proteins

Abstract: A new algorithm, called convex constraint analysis, has been developed to deduce the chiral contribution of the common secondary structures directly from experimental CD curves of a large number of proteins. The analysis is based on CD data reported by Yang, J.T., Wu, C.-S.C. and Martinez, H.M. [Methods Enzymol., 130, 208-269 (1986)]. Application of the decomposition algorithm for simulated protein data sets resulted in component spectra [B (lambda, i)] identical to the originals and weights [C (i, k)] with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
263
0
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(273 citation statements)
references
References 0 publications
6
263
0
4
Order By: Relevance
“…In assessing factors that affect the stability of a-helices and coiled coils, it is important to realize that they are different structures and that their conformational transitions are not necessarily linked. The results also emphasize the utility of the convex constraint algorithm of Perczel et al (1991) for evaluating the contribution of different secondary structures to CD spectra.…”
Section: Discussionmentioning
confidence: 63%
“…In assessing factors that affect the stability of a-helices and coiled coils, it is important to realize that they are different structures and that their conformational transitions are not necessarily linked. The results also emphasize the utility of the convex constraint algorithm of Perczel et al (1991) for evaluating the contribution of different secondary structures to CD spectra.…”
Section: Discussionmentioning
confidence: 63%
“…3e) (monomeric Aβ is not detectable by TEM). Circular dichroism (CD) analysis followed by spectra deconvolution using CCA + software Lincomb algorithm 81,82 was carried out to assess the secondary structure elements of the Aβ fractions. CD analysis of this preparation showed a spectrum with minima at ~195-205 nm, consistent with a predominantly random coil conformtion (supplementary Fig.…”
Section: |mentioning
confidence: 99%
“…CD spectra deconvolution, carried out using the CCA + software Lincomb algorithm 81,82 , showed that the protofibrils, obtained using this protocol, consisted of 43% β-sheet, 38% α-helix and 5% random coil as secondary structure elements (supplementary Fig. 1a).…”
Section: |mentioning
confidence: 99%
“…The deconvoluted basis curves, each of which has a unique shape, can be associated with a known mixture of secondary structures and can therefore be used to analyze the conformation of an unknown sample. Convex constraint analysis (CCA) has also been used to extract basis spectra (Perczel et al, 1991).…”
Section: A Secondary Structure Content Of Proteinsmentioning
confidence: 99%